1997
DOI: 10.1046/j.1365-2958.1997.3411711.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial pathogenesis in cystic fibrosis: co‐ordinate regulation of heat‐shock response and conversion to mucoidy in Pseudomonas aeruginosa

Abstract: SummaryConversion of Pseudomonas aeruginosa to the mucoid phenotype plays a major role in the pathogenesis of respiratory infections in cystic fibrosis (CF). One mechanism responsible for mucoidy is based on mutations that inactivate the anti-factor, MucA, which normally inhibits the alternative sigma factor, AlgU. The loss of MucA allows AlgU to freely direct transcription of the genes responsible for the production of the exopolysaccharide alginate resulting in mucoid colony morphology. In Escherichia coli, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 54 publications
3
57
1
Order By: Relevance
“…This contrasts with the demonstrated involvement of AlgU in tolerance towards these stresses in P. aeruginosa (32,54,56,70) and in P. syringae (26). Activation of algU by ROIs may help these pathogens withstand the oxidative burst associated with host defense responses (19,26).…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…This contrasts with the demonstrated involvement of AlgU in tolerance towards these stresses in P. aeruginosa (32,54,56,70) and in P. syringae (26). Activation of algU by ROIs may help these pathogens withstand the oxidative burst associated with host defense responses (19,26).…”
Section: Discussioncontrasting
confidence: 46%
“…In P. aeruginosa, the algU, mucA, and mucB genes are cotranscribed and encode (respectively) the sigma factor AlgU and its main negative regulators, MucA and MucB, which act in concert to control production of the EPS alginate and the response to extreme environmental stress (19,32,50,54,57,70). In P. syringae, AlgU is also a major determinant in the regulation of alginate biosynthesis and stress response (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In P. aeruginosa it was shown that AlgT directs transcription of a large set of virulence determinants or toxic factors (Firoved et al, 2002;Firoved & Deretic, 2003) and of the gene encoding the main heat-shock factor RpoH (Schurr & Deretic, 1997). Microarray analysis revealed that AlgT exerts broad-range regulatory effects on approximately 6 % of the P. aeruginosa genome, with alginate and flagellar genes accounting for only one-fifth of AlgT-regulated genes (Tart et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The alginate biosynthetic operon in P. aeruginosa is controlled by several two-component systems and by the alternative sigma factor, AlgT (Mathee et al, 2002). AlgT of P. aeruginosa acts as a global stress response sigma factor that activates transcription of the main heat-shock sigma factor RpoH, as well as different virulence determinants or toxic factors (Firoved et al, 2002;Firoved & Deretic, 2003;Schurr & Deretic, 1997). AlgT in P. syringae (s 22 ) is encoded by the first gene of the algT-mucAB operon, which activates alginate biosynthesis by activating its own transcription and that of algD (Keith & Bender, 1999;Schenk et al, 2006).…”
Section: Introductionmentioning
confidence: 99%